2019
DOI: 10.1080/02770903.2018.1553050
|View full text |Cite
|
Sign up to set email alerts
|

Key factors associated with uncontrolled asthma – the Asthma Control in Latin America Study

Abstract: Objective: This study aimed to estimate asthma control at specialist treatment centers in four Latin American countries and assess factors influencing poor asthma control. Methods: Patients aged !12 years with an asthma diagnosis and asthma medication prescription, followed at outpatient specialist centers in Argentina, Chile, Colombia, and Mexico, were included. The study received all applicable ethical approvals. The Asthma Control Test (ACT) was used to classify patients as having controlled (ACT 20-25) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 41 publications
5
23
1
5
Order By: Relevance
“…Negative coefficients for median family income and percent of older housing indicate that residents in lower income or older census blocks experience greater numbers of asthma admissions than other people holding other variables constant. This is consistent with recent studies in the U.S. and abroad that continue to highlight problems with asthma management among socioeconomically stressed patients (Bryant‐Stephens et al, ; Neffen et al, ). Coefficients for average speed on road segments and road density suggest that greater levels of traffic in the census block group predict greater use of hospital and ED services for asthma exacerbations holding other variables constant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Negative coefficients for median family income and percent of older housing indicate that residents in lower income or older census blocks experience greater numbers of asthma admissions than other people holding other variables constant. This is consistent with recent studies in the U.S. and abroad that continue to highlight problems with asthma management among socioeconomically stressed patients (Bryant‐Stephens et al, ; Neffen et al, ). Coefficients for average speed on road segments and road density suggest that greater levels of traffic in the census block group predict greater use of hospital and ED services for asthma exacerbations holding other variables constant.…”
Section: Discussionsupporting
confidence: 91%
“…Data regarding sex shows that adult males are less likely than adult females to be admitted for a primary diagnosis of asthma holding other variables constant. The positive relationship between adult women and asthma incidence or prevalence has been consistently documented for many years and in various countries (Habib, Javer, & Buxton, ; Jeebhay, Ngajilo, & le Mousal, ; Neffen et al, ). This relationship contrasts with the development of asthma in children where males are more often affected than females.…”
Section: Discussionmentioning
confidence: 90%
“…In our population of asthmatics who required any hospital readmission, more than 71% were obese or overweight, but this is not associated with the incidence of hospital readmissions. Our results are in agreement with the other authors who did not observe a relationship between obesity and exacerbations or with the control of the asthma [8,16,21,[29][30][31], although it was different from other studies where we showed a poorer control of asthma or increase in the incidence of the exacerbations with obesity [13][14][15]19,20,[32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, they don´t have more frequent readmissions during the follow-up period. In the literature, asthma exacerbations requiring hospital admission are usually a minority, since most patients are discharged from the Emergency Room [14,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation